Penerapan Metode Permainan Teknik Bingo Review untuk Meningkatkan Aktivitas Belajar Peserta Didik dalam Pembelajaran Sejarah - Rika Aryani; Tarunasena Ma'mur (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
This thesis entitled “Application of the Bingo Review Technique game Method to Improve Student Activities in Learning History (Classroom Action Research in Class XI IPS 2 SMA Negeri Tanjungsari)”. This research aims to increase students’ activity with the adoption of a bingo game. History subject are considered boring subject, old-fashioned and monotonous, so most students are not interested, no excited, indifferent and do not care to follow the history of the learning process. This shows that students’ learning activities are low. The research method used was the Classroom Action Research (CAR) method using research designs from Kemmis and Taggart. This design consists of 4 phases: planning (plan), implementation (act), observation (observ) and reflection (reflect) in cycle. Based on the research that has been done, the development of students in achieving the criteria on the predetermined learning activity indicators has increased in each cycle. This shows that in implementing the bingo review technique game method to improve student learning activities is one way solution for fun learning activity. This research can be a recommendation for schools, teachers and researchers to develop more innovative, interesting and fun history learning process so that it can increase students’learning activities.